Responding to Xenophobic Violence in Post-Apartheid South Africa: Barking Up the Wrong Tree? - Jean Pierre Misago (African Human Mobility Review, 2021)
This paper highlights the general failure to effectively respond to and prevent xenophobic violence in South Africa and offers critical reflections on reasons thereof. Drawing mainly on the evaluation of a number of anti-xenophobic programmes by government and civil society organisations, the paper argues that past and current interventions, instead of muzzling dogs that bite, have been rather barking up the wrong tree. National government and relevant local authorities have thus far either tended to ignore the problem or categorise violence against foreign nationals and other outsiders as normal crime with no need for more specific or more targeted interventions. Although well-intentioned, civil society efforts to foster peaceful cohabitation and tolerance through social dialogues and campaigns aimed at changing attitudes have also largely proven ineffective in reducing violence. There are many reasons why these interventions continue to fail. Chief among these reasons is the fact that interventions are not evidence-based and are not informed by a clear understanding of the drivers of the violence. Similarly, past and current responses and interventions are based on shaky foundations and untested theories of change. Indeed, by focussing almost exclusively on public attitudes, interventions neglect factors and motivations that trigger violent behaviour; perhaps ignoring that attitudes are not always a good predictor of behaviour. Without a clear understanding of the drivers of the violence and of what type of responses work or do not work, intervention strategies can only be ineffective at best, and counter-productive at worst.